The impact of the changing pneumococcal national immunisation program among older Australians. Issue 4 (22nd January 2021) - Menzies, R.; Stein, AN.; Booy, R.; Van Buynder, PG.; Litt, J.; Cripps, AW.
Abstract: Australia has a universal infant pneumococcal conjugate vaccination program and until recently a universal pneumococcal polysaccharide vaccine program for non-Indigenous adults aged ≥65 years and Indigenous adults aged ≥50 years. We documented the impacts of infant and adult vaccination programs on the epidemiology of invasive pneumococcal disease (IPD) in Indigenous and non-Indigenous adults. IPD notifications from the National Notifiable Disease Surveillance System were analysed from 2002 to 2017, grouped by age, vaccine serotype group and Indigenous status. Since the universal funding of infant and elderly pneumococcal vaccination programs in January 2005, total IPD decreased by 19% in non-Indigenous adults aged ≥65 years but doubled in Indigenous adults aged ≥50 years. Vaccine uptake was suboptimal in both groups but lower in Indigenous adults. IPD due to the serotypes contained in the pneumococcal conjugate vaccines (PCV) except for serotype 3 declined markedly over the study period but were replaced by non-PCV serotypes. Serotype 3 is currently the most common in older adults. In the populations eligible for the adult 23-valent pneumococcal polysaccharide vaccine (23vPPV) program, IPD rates due to its exclusive serotypes increased to a lower extent than non-vaccine types. In 2017, non-vaccine serotypes accounted for most IPD in the older population eligible for the 23vPPV program, while it's eleven exclusive serotypes accounted for the majority of IPD in younger adults. Infant and adult pneumococcal vaccination programs in Australia have shaped the serotype-specific epidemiology of IPD in older adults. IPD remains a significant health burden for the Indigenous population. Herd immunity impact is clear for PCV serotypes excluding serotype 3 and serotype replacement is evident for non-PCV serotypes. The adult 23vPPV immunisation program appears to have partially curbed replacement with IPD due to its eleven exclusive serotypes, highlighting a potential benefit of increasing adult 23vPPV coverage in Australia.